Pengaruh Motivasi, Lingkungan Keluarga, Biaya Pendidikan pada Minat Mahasiswa Mengikuti Pendidikan Profesi Akuntansi - Paramesti Ningrat, Ida Ayu Ardhia; Krisna Dewi, Luh Gede (E-Jurnal Akuntansi; Vol 30 No 7 (2020)DO - 10.24843/EJA.2020.v30.i07.p06, 2020)
Accounting Study Program experiences continuous development, but there are only a few students who are interested in continuing into Professional Accounting Education. The research aims to examine the influence of career motivation, economic motivation, family environment, and perceptions of educational costs on students' interest to study at Accounting Professional Education. Study conducted at the Faculty of Economics and Business, Udayana University. The sample are students at accounting regular program class of 2016, with 181 respondents using simple random sampling. Data collected by questionnaire and analyzed by multiple linear regression. Based on the results, career motivation, economic motivation, family environment, and perceptions of educational costs have a positive effect on student interest in taking the Accounting Professional Education. Keywords: Career Motivation; Economic Motivation; Family Environment; Perceived Education Costs.